Liver Protective Effect of Fenofibrate in NASH/NAFLD Animal Models - Ali Mahmoudi; Seyed Adel Moallem; Thomas P. Johnston; Amirhossein Sahebkar (PPAR Research)
Nonalcoholic fatty liver disease (NAFLD) is initiated by excessive fat buildup in the liver, affecting around 35% of the world population. Various circumstances contribute to the initiation and progression of NAFLD, and it encompasses a wide range of disorders, from simple steatosis to nonalcoholic steatohepatitis (NASH), cirrhosis, and liver cancer. Although several treatments have been proposed, there is no definitive cure for NAFLD. In recent decades, several medications related to other metabolic disorders have been evaluated in preclinical studies and in clinical trials due to the correlation of NAFLD with other metabolic diseases. Fenofibrate is a fibrate drug approved for dyslipidemia that could be used for modulation of hepatic fat accumulation, targeting peroxisome proliferator-activator receptors, and de novo lipogenesis. This drug offers potential therapeutic efficacy for NAFLD due to its capacity to decrease the accumulation of hepatic lipids, as well as its antioxidant, anti-inflammatory, and antifibrotic properties. To better elucidate the pathophysiological processes underlying NAFLD, as well as to test therapeutic agents/interventions, experimental animal models have been extensively used. In this article, we first reviewed experimental animal models that have been used to evaluate the protective effects of fenofibrate on NAFLD/NASH. Next, we investigated the impact of fenofibrate on the hepatic microcirculation in NAFLD and then summarized the beneficial effects of fenofibrate, as compared to other drugs, for the treatment of NAFLD. Lastly, we discuss possible adverse side effects of fenofibrate on the liver.